Avaliação da concentração de retinol em fígados frescos e congelados de frangos das linhagens Cobb e Ross - Santos, Videanny Videnov Alves dos (2008)
The intake of adequate quantities of food, including those rich in vitamins, is necessary for a healthy life. The lack of vitamin A has been characterized as a public health problem in developing countries, however, a high intake of vitamin A can result in toxic and teratogenics effects. High concentrations of vitamin A have been observed in the livers of animals. The objective of this study was to assess the levels of retinol in chicken livers and verify the effect of frozen storage on these levels. 64 livers from two chicken strains, Cobb and Ross, were used, came from four different farms. We examined 32 livers from each strain, 8 samples from each farm. Liver sample were homogenized individually, then 4 aliquots were taken from each sample. One of aliquots was analyzed immediately after slaughter (T0), the others were analyzed after 30, 60 and 90 days of storage at -18oC (T30, T60 and T90, respectively). Retinol dosage in the liver was determined by High Performance Liquid Chromatography (HPLC). The levels of retinol varied significantly according to the strain. The mean retinol value in the fresh samples was 6678.0 ± 1337.7 and 8324.1 ± 1158.5 µg/100g in the Cobb and Ross strain, respectively. Values of 4258 ± 918.7 ± 1391.7 and 4650.5 ± 1391.7 μg/100g were found after 90 days of storage for Cobb and Ross strain, respectively. The liver freezing caused a significant reduction in their levels of retinol, causing a loss of up to 44% with respect to fresh livers. The reduction in retinol levels occurred from 30 days of storage. Even with the losses from the frozen, the ingestion of a typical portion of 100 g of liver, regardless the chicken strain analyzed, surpass all recommendations of consumption and the maximum tolerable intake of vitamin A (3000 μg/day) for adults